Current Understanding of Long-Term Cognitive Impairment After Sepsis - Li, Ying; Ji, Muhuo; Yang, Jianjun (Frontiers in Immunology, 2022)
Sepsis is recognized as a life-threatening multi-organ dysfunction resulting from a dysregulated host response to infection. Although the incidence and mortality of sepsis decrease significantly due to timely implementation of anti-infective and support therapies, accumulating evidence suggests that a great proportion of survivors suffer from long-term cognitive impairment after hospital discharge, leading to decreased life quality and substantial caregiving burdens for family members. Several mechanisms have been proposed for long-term cognitive impairment after sepsis, which are not mutually exclusive, including blood-brain barrier disruption, neuroinflammation, neurotransmitter dysfunction, and neuronal loss. Targeting these critical processes might be effective in preventing and treating long-term cognitive impairment. However, future in-depth studies are required to facilitate preventive and/or treatment strategies for long-term cognitive impairment after sepsis.